Quasi conformally flat quasi Einstein Weyl manifolds - NURCAN, AYŞE FÜSUN (Intechopen, 2022)
The aim of this work is to study on quasi conformally flat quasi Einstein-Weyl manifolds. In this book chapter, firrstly, an interesting relationship between complementary vector field and generator of the quasi Einstein-Weyl manifold is obtained and supported by an example. Then, it is investigated that quasi conformally flat quasi Einstein-Weyl manifolds are of quasi constant curvature, recurrent and semi-symmetric under which conditions after obtaining the expression of the curvature tensor of the quasi conformally flat quasi Einstein-Weyl manifold. Furthermore, some equivalences are obtained between to be of quasi constant curvature and to be semi-symmetric in quasi conformally flat quasi Einstein-Weyl manifolds
Keywords: Temel Bilimler; Natural Sciences; Temel Bilimler (SCI); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; MULTIDISCIPLINARY SCIENCES; Multidisipliner; Multidisciplinary